PERENCANAAN JEMBATAN BOX GIRDER DI TANGGUL LAUT KEC. SUNGAI KAKAP - Mulyana, Nauval; Yusuf, M.; Aryanto, Aryanto (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2024)
projected traffic flow in the form of an increase in vehicle volume every year and to eliminate conflicts to connect the Rengas River and the Berembang River in Sungai Kakap District, Kubu Raya Regency makes planning a reinforced concrete bridge the preferred solution and is planned as a class 1 bridge which must have a traffic design load of 100% of the total load. With a traffic lane width of 8.00 m using 1 unit of Box Girder with 2 Hollows with a bridge span of 36 m with specifications: girder height 3.00 m, bridge width 10 m, prestressed concrete quality box girder (fc' = 41.50 MPa), and the quality of the bridge floor slab/concrete (fc' = 41.50 MPa).Based on the results of calculations and analysis, the initial prestressing force was 28,138.94 kN, experiencing a total prestress loss of 17.48% so that the remaining stress was 18,524.56 kN from the prestressing force due to jacking force of 22,449.41 kN.. In one section of the box girder using tendons prestressing consists of: 3 tendons with nominal diameter specifications of strands of 12.7 mm (0.5") totaling 7 uncoated type wires 7 super wire strands ASTM A-416-06 grade 270  Key Words: box girder bridges, prestress loss, prestressed concrete, tendon placemen